The Influence of Organizational Culture, Morals and Leadership Style on Employee Performance - Ayunda, Antin; Marliyah, Marliyah; Rahma, Tri Inda Fadhila (Almana : Jurnal Manajemen dan Bisnis, 2025)
Employee performance is the main factor in the success of a company, including in the plantation sector which has a field-based, hierarchical work system. PT. Perkebunan Nusantara IV The Tobasari is a state-owned company that implements the AKHLAK organizational culture (Trusted, Competent, Harmonious, Loyal, Adaptive, and Competent) to improve employee performance, but its implementation has not been evenly distributed to all employees. The purpose of this study was to analyze the effect of AKHLAK Organizational Culture and Leadership Style on Employee Performance at PT. Perkebunan Nusantara IV The Tobasari. The research method used was quantitative, with data collection techniques through distributing questionnaires to 62 employees of PT. Perkebunan Nusantara IV The Tobasari as respondents. Data analysis was carried out using the Partial Least Square (PLS) method based on Structural Equation Modeling (SEM) to analyze the relationship between variables. The results of the study showed that AKHLAK organizational Culture had a positive and significant effect on employee performance at PT. Perkebunan Nusantara IV The Tobasari. Meanwhile, Leadership Style did not show any effect on employee performance at PT. Perkebunan Nusantara IV The Tobasari. The findings in this study indicate that employees are more influenced by work culture than by leadership style.